Foreign Direct Investment and Economic Growth: Evidence from United Kingdom - Obinna, Osuji Christian; Chinweizu, Alugbuo Justin; Emeka, Eze (International Journal of Economics and Financial Issues, 2025)
The study examined the relationship between foreign direct investment (FDI) and economic development in the United Kingdom using annual time series data from the World Bank spanning the years 1981-2021. The data was analyzed using the Auto-regressive distributed lag model (ARDL) and the Toda-Yamamoto causality test. The study’s two main empirical findings were that, first, foreign direct investment and UK economic growth were positively correlated, and, second, that, in contrast to common opinion, strong economic growth stimulates the inflow of foreign direct investment. Therefore, it was suggested that the government of the United Kingdom and its policy makers should open up additional channels to draw in international investors in order to facilitate knowledge transfer, generate employment opportunities, and boost productivity. This can be achieved by providing unique FDI packages to international businesses, which may include reduced income taxes or income tax holidays, import duty exemptions, and infrastructure subsidies.